2009
DOI: 10.1097/gme.0b013e3181a5d0d6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subjective and objective hot flash measures over time among breast cancer survivors initiating aromatase inhibitor therapy

Abstract: Objective-Hot flashes are valuable indicators of physiologic condition and drug effect; however, subjective and objective measures do not always agree. No study has examined both subjective and objective hot flashes in women prescribed aromatase inhibitors. The study (1) compared subjective and objective hot flash measures, (2) examined changes in subjective and objective hot flashes over time, and (3) evaluated predictors of change in hot flashes in aromatase inhibitor-treated women.Design-Subjects (n=135) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…While higher than reported by clinical trial data in BCS [9], this prevalence is similar to smaller observational studies of BCS [1,2] and the general menopausal population [20]. Data on whether AI therapy is associated with higher risk of hot flashes is conflicting [9,21]. Nonetheless, this high prevalence indicates that hot flashes are a common problem for the growing population of BCS on AI therapy.…”
Section: Discussionmentioning
confidence: 50%
“…While higher than reported by clinical trial data in BCS [9], this prevalence is similar to smaller observational studies of BCS [1,2] and the general menopausal population [20]. Data on whether AI therapy is associated with higher risk of hot flashes is conflicting [9,21]. Nonetheless, this high prevalence indicates that hot flashes are a common problem for the growing population of BCS on AI therapy.…”
Section: Discussionmentioning
confidence: 50%
“…Kim et al 39 assessed hot flashes by using Mexameter, Skin Thermometer, Corneometer, and Laser Doppler Perfusion Imager objectively, and results indicated weak correlation between subjective and objective measurements of hot flashes. Although previous studies show no objective measures of changes in hot flashes, [37][38][39] the authors tried to include objective measure to explain the phenomena of hot flashes. On the basis of the findings that the subjective sensation of Heat is the predominant feature of a hot flash, infrared thermography was used.…”
Section: Discussionmentioning
confidence: 99%
“…37 There are several studies to compare subjective and objective method for assessing hot flashes. [37][38][39] Carpenter et al 37 and Otte et al 38 assessed hot flash frequency using self-report and sternal skin conductance monitoring, and the findings indicated dissimilarities between subjective and objective measures. Kim et al 39 assessed hot flashes by using Mexameter, Skin Thermometer, Corneometer, and Laser Doppler Perfusion Imager objectively, and results indicated weak correlation between subjective and objective measurements of hot flashes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either original Kupperman index or complicated QOL questionnaires [27] , they are in the category of subjective measurement. One randomized clinical trial compared subjective and objective hot flash measures [40] among breast cancer survivors initiating aromatase inhibitor therapy. A sternal skin conductance monitor was used in trial to provide objective measure of hot flashes; findings indicated dissimilarities between subjective and objective measures of hot flashes.…”
Section: Discussionmentioning
confidence: 99%